Nerd-Chic Look— Cultural Capital and Signs in the Relationship of Knowledge and Power - Chen, Kezhu (Transactions on Social Science, Education and Humanities Research, 2025)
In contemporary media and fashion discourse, the image of “nerd” has undergone a significant transformation —from a marginalized character to a symbol of authority and appeal in films and television. This article analyzes the Nerd-chic style of Sheldon from The Big Bang Theory, Sherlock Holmes from Sherlock, and the menswear outfits worn by Annie in Annie Hall as case studies, by combining with Foucault’s theory of power and knowledge to further fill the existing gaps in the field also with the supplement the concepts of cultural capital, consumption symbols, and power discourse. The cases examined on the formation of the Nerd-chic look indicate that intelligence has become a symbol of cultural capital, and consumers purchase these signs to construct their own social discourse power. This study combines media narrative with fashion semiotics to fill a gap in academic research on the sociocultural construction of knowledge elitism and its gendered and symbolic fashion expressions. Furthermore, it offers a new perspective on understanding how knowledge and power intersect through fashion and symbolism within popular culture.